Seawater Desalination Using Waste Heat Recovery on Passenger Ship - Arwa Hussein; Hasnaa Kandil (Port Said Engineering Research Journal, 2020)
This paper presents a study for sea water desalination on board of passenger ships using waste heat from the engine. Three thermal methods for water desalination were explored, namely Forward Feed Multiple Effect Evaporation, Once Through Multi-Stage Flash, and Brine Circulation Multi-Stage Flash. Computer simulation has been developed to calculate the parameters of the desalination plant; the required amount of fresh water and the corresponding total heat transfer area. The optimum plant selection is the one which achieves the required distillate flow rate with minimum heat transfer area. The effect of different variables on the plant selection has been studied, i.e. steam temperature, exhaust temperature, and intake water flow rate. An existing passenger ship has been selected to examine the proposed method where the optimum desalination method has been selected for her using the developed software. To assess the effectiveness of the proposed method, the economical, environmental, and technical gains are numerically analyzed. Using the waste heat recovery leads to reducing the unit product cost of freshwater by circa 30%. The plant reduced the emissions by about five thousand tons of CO2, 100 tons of NOx and 35 tons of SO2 per year. Applying the optimum design of the proposed salt water desalination on the case study saved 2.7 $/ m3 as a minimum comparing to the average cost of fresh water in ports. These savings can cover the plant capital cost in six years at most.